In vitro affinity optimization of an anti-BDNF monoclonal antibody translates to improved potency in targeting chronic pain states in vivo. Issue 1 (1st January 2020) - Stack, Edwina; McMurray, Sheridan; McMurray, Gordon; Wade, Jason; Clark, Melissa; Young, Gareth; Marquette, Kim; Jain, Sadhana; Kelleher, Kerry; Chen, Ting; Lin, Qingcong; Bloom, Laird; et al.
ABSTRACT: The role of brain-derived neurotrophic factor (BDNF) signaling in chronic pain has been well documented. Given the important central role of BDNF in long term plasticity and memory, we sought to engineer a high affinity, peripherally-restricted monoclonal antibody against BDNF to modulate pain. BDNF shares 100% sequence homology across human and rodents; thus, we selected chickens as an alternative immune host for initial antibody generation. Here, we describe the affinity optimization of complementarity-determining region-grafted, chicken-derived R3bH01, an anti-BDNF antibody specifically blocking the TrkB receptor interaction. Antibody optimization led to the identification of B30, which has a > 300-fold improvement in affinity based on BIAcore, an 800-fold improvement in potency in a cell-based pERK assay and demonstrates exquisite selectivity over related neurotrophins. Affinity improvements measured in vitro translated to in vivo pharmacological activity, with B30 demonstrating a 30-fold improvement in potency over parental R3bH01 in a peripheral nerve injury model. We further demonstrate that peripheral BDNF plays a role in maintaining the plasticity of sensory neurons following nerve damage, with B30 reversing neuron hyperexcitability associated with heat and mechanical stimuli in a dose-dependent fashion. In summary, our data demonstrate that effective sequestration of BDNF via a high affinity neutralizing antibody has potential utility in modulating the pathophysiological mechanisms that drive chronic pain states.